Characterization of Antixenosis in Soybean Genotypes to Bemisia tabaci (Hemiptera: Aleyrodidae) Biotype B - Baldin, E. L. L. [UNESP]; Cruz, P. L.; Morando, R. [UNESP]; Silva, I. F. [UNESP]; Bentivenha, J. P. F.; Tozin, L. R. S. [UNESP]; Rodrigues, T. M. [UNESP] (Oxford Univ Press Inc, 2017)
Bemisia tabaci biotype B (Gennadius) is one of the most important soybean pest worldwide. Herein, 15 soybean genotypes were evaluated, to characterize the occurrence of antixenosis to B. tabaci biotype B. Initially, a multiple-choice test with all genotypes was carried out, evaluating the settling and oviposition preference at 3 d after infestation, and the colonization by nymphs after 48 d of infestation. Subsequently, a no-choice test, using 14 genotypes, was conducted with infested plants individually, and the number of eggs was counted after 72 h. Then, 10 genotypes were selected (indicative of resistance and susceptibility), which were evaluated for whitefly settling 24, 48, and 72 h after infestation and for oviposition 72 h after infestation. The trichomes of the leaflets were characterized for density, size, and inclination to establish possible correlations with the settling and oviposition in the genotypes. In the first multiple-choice test, involving 15 genotypes, 'IAC-17,' 'IAC-19,' and UX-2569-159 expressed antixenosis against B. tabaci. 'Jackson,' 'P98Y11,' and PI-229358 exhibited the same behavior in the no-choice test. In the multiple-choice test, 'Jackson,' 'P98Y11,' and 'TMG1176 RR' were the least attractive and least used for oviposition. The antixenosis shown by 'Jackson,' 'P98Y11,' and PI-229358 may be related to the characteristics of the trichomes (lower density and inclined). Based on the experiments carried out, 'IAC-17,' 'IAC-19,' 'Jackson,' 'P98Y11,' PI-229358, TMG1176 RR, and UX-2569-159 are considered promising for resistance to B. tabaci biotype B and may be exploited in soybean breeding programs for resistance to insects.
Keywords: sweetpotato whitefly; host plant resistance; nonpreference; trichome